OTONOMI DAERAH DAN PELUANG INVESTASI UNTUK PERCEPATAN PEMBANGUNAN - Sugianto, Bambang; Kurniawati, Dita; Abbas, Zakaria (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2020)
Abstrak Tujuan Otonomi daerah memberikan kemudahan daerah dalam melaksanakan kewenangan, sehingga dalam menjalankan kewenangan membawak efek positif dalam berinvestasi. Investasi bertujuan untuk peningkatan ekonomi masyarakat daerah serta peningkatan Pendapatan Daerah, tetapi otonomi sering disalahgunakan oleh Pemerintah daerah terutama yang berhubungan dengan perizinan, sehingga Investor mengalami kesulitan dan hambatan. Tujuan otonomi daerah supaya ada dampak positif serta memberi pelayan publik lebih mudah dan cepat, penyederhanaan Pelayanan Kegiatan Investasi, dan penyederhanaan (regulasi) pelayanan kegiatan ekonomi membantu kelancaran usaha dari para pelaku ekonomi, karena deregulasi dipandang untuk meningkatkan efisiensi bagi pelaku ekonomi. Adanya kepastian proses adminitrasi dan kepastian hukum yang dapat menjamin keamanan dan stabilitas politik Daerah, singkronisasi regulasi antar pemerintah daerah dengan pemerintah pusat, Daerah harus membuka diri dan mempermudah perizinan sektor investasi terutama berhubungan rekruitmen tenaga kerja yang besar, terukurnya kemampuan keuangan daerah dalam era otonomi daerah dengan menggunakan kinerja fiscal sehingga tercapainya keberhasilan daerah dalam menjalani otonomi daerah. Kata Kunci: Otonomi Daerah, Investasi. Abstract In doing investment, there are often problems, one of which is regional autonomy, the challenges of implementing investment in Indonesia in the era of regional autonomy in Indonesia. In its regulation, there is a system of division of authority in facilitating the entry of investments with the investment arrangements at the regional level referring to investment regulations at the national level. Therefore, although the direction of Indonesian economy after Regional Autonomy refers to the economy in the region, it must be remembered that the authority of regional autonomy towards regional independence remains within the framework of the unitary state. The direction of the investment policy and the increase in business activities through investment policies are expected to create opportunities for the growth and development of the business world for every large, medium, and small scale of economic actor. Simplification of Investment Services, Simplification (deregulation) economic activity services helps accelerate the operation of economic actors, because deregulation is seen to increase efficiency for economic actors. The certainty of the administrative process and legal certainty that can guarantee the security and political stability of the region, synchronization of regulations between the local government and the central government, faster in licensing and the realization of certainty, the regional government must open up and facilitate licensing of the investment sector, especially related to the large recruitment of workers, measurable regional financial capacity in the era of regional autonomy by using performance so that the regional achievement can successfully undergone the regional autonomy.